Effects of aging and exercise training on the common carotid blood velocities in healthy men - Azhim, Azran; Akioka, Kohei; Akutagawa, Masatake; Hirao, Yuji; Yoshizaki, Kazuo; Obara, Shigeru; Nomura, Masaharu; Tanaka, Hiroyuki; Yamaguchi, Hisao; Kinouchi, Yohsuke (2007)
An age-related alteration in the cardiovascular response to exercise training are evident. The purpose of the study was to investigate the effects of exercise and age on blood velocities in common carotid artery in 82 healthy men between the age ranges of 21 to 67 years old. Blood velocities are characterized to five components of velocity waveforms as peak systolic (S1), second systolic (S2), incisura between systole and diastole (I), peak diastolic (D) and end-diastolic velocity wave (d). Decrease of blood velocities in peak systolic (r= -0.711, P<0.0001) and in peak diastolic velocities (r= -0.521, P<0.0001) with aging are improved and partially restore in particularly older men. The velocity ratio of S2/S2-1 as a reflection index increase with age (r= 0.797, P<0.0001), however is smaller in exercise-trained older compared with sedentary peers. The ratio of 1-I/D as a vascular elastic recoil index decrease with aging (r= -0.640, P<.0001), but is relatively higher in exercise-trained men. Exercise training improves the age-related deterioration in blood velocities and its indices in healthy men. In the further investigations, the assessment of aerobic fitness and vascular aging has potential by using the criteria of peak systolic and peak diastolic, and its indices.